IMPROVING THE METHODOLOGY FOR TRANSFORMING THE INSURANCE MARKET UNDER CONDITIONS OF ECONOMIC GLOBALIZATION AND DIGITALIZATION - Nomozova Qumri Isoyevna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
The paper substantiates an enhanced methodology for analysing insurance market transformation under economic globalisation and digitalisation, with Uzbekistan as the case context. It argues that transformation assessment should extend beyond volume-based indicators (premiums, assets, number of firms) and incorporate digital maturity, customer outcomes, operational efficiency, and risk governance. Using official market statistics and regulator-reported indicators, the study documents shifts in premium and claims dynamics, as well as structural changes related to consolidation, distribution reconfiguration, and the strengthening of actuarial capacity. An integrated analytical framework is proposed to connect insurers’ digital capability building with sustainable competitiveness and supervisory objectives.